Primal Conflicts and Silent Reverberations: Ecocriticism and Digital Media in Jallikattu and Ee.Ma.Yau. (International Journal of Scientific Research in Science and Technology, 2024)
In the Anthropocene age, characterized by ecological catastrophes and technological advancement, cinema serves as a vital medium to examine humanity’s intricate interaction with the natural environment. This study examines the Malayalam films Jallikattu (2019) and Ee.Ma.Yau (2018) as significant ecocritical works that integrate regional cultural narratives with the global conversation on environmental ethics, situated within the framework of digital culture.Directed by Lijo Jose Pellissery, Jallikattu explores the turmoil that ensues as a liberated buffalo rampages through a community, serving as a vivid analogy for humanity’s avarice and the resultant ecological disruption. The film’s rapid pacing and digitally enhanced images intensify the fundamental conflict between human supremacy and nature’s intrinsic opposition. Conversely, Ee.Ma.Yau presents a contemplative examination of mortality and ecological interconnectedness, situated in a coastal community where nature quietly observes human existence and ceremonies. The sparse narrative, contrasted with the digitally immersive depiction of coastal ecosystem, highlights the pervasive influence of natural forces on human existence. This study utilizes theoretical frameworks like deep ecology, posthumanism, and media ecology to analyze how these films critique anthropocentrism while employing digital tools to enhance ecological awareness. By placing these cinematic texts within the wider cultural and environmental discourse, the research highlights their dual function as regional representations and universal critiques of humanity’s troubled connection with the environment. This interdisciplinary investigation underscores cinema’s capacity to enhance environmental consciousness in a digitally networked society.